Perencanaan Media Pembelajaran Sambungan dan Hubungan Kayu Berbasis Tik pada Mata Pelajaran Produktif Teknik Furnitur - Abu Bakar Rianto; Arris Maulana; Risdian M Noor (Jurnal Pensil : Pendidikan Teknik Sipil, 2012)
This innovative work undertaken in order to improve the quality of student learning outcomes and create new experiences for learners in learning process for the course of Furniture Construction especially for the subject of Timber Connection and Assembling. This innovative work was tested at SMK Negeri 52 Jakarta. The method of this innovative work is done based on seven stages. Those seven stages are observation (data collective), preparation of materials, information flow preparation, data compilation, initial development, evaluation and ending development. Evaluation process carried out by two phases, validation and revision. Validation phase was conducted by media expertise from the Center for Learning Resources (PSB) and for the content and instructional expertise conducted by two teachers for the course of Furniture Construction especially for the subject of Timber Connection and Assembling in SMK Negeri 52 Jakarta. From the calculation of the media expertise, we get the average of 4.5 total validations. It indicates that the media; if we viewed from the range 4.5 ≤ x ≤ 5; is accepted into the criteria of excellent value. From the calculation and validation of instructional substance expertise, we obtained the average total validation of 4.425. If we analyze from the range 3.5 ≤ x  4.5, then the value is accepted into the good criterion. Learning outcomes from students in class X TF B SMK Negeri 52 Jakarta using this method showed an increasing value by the average of 76.23 from the scale of 1-100 on the Basic Competency-8, Timber Connection and Assembling